2019
DOI: 10.3390/molecules24183254
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Whey Protein-Based Nano-Delivery Systems: A Review

Abstract: Various bioactive compounds (BCs) often possess poor stability and bioavailability, which makes it difficult for them to exert their potential health benefits. These limitations can be countered by the use of nano-delivery systems (NDSs), such as nanoparticles and nanoemulsions. NDSs can protect BCs against harsh environments during food processing and digestion, and thereby, could enhance the bioavailability of BCs. Although various NDSs have been successfully produced with both synthetic and natural material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 93 publications
(192 reference statements)
0
33
0
2
Order By: Relevance
“…On the other hand, the aggregation capability of proteins from natural sources is used to generate nanoparticles for drug-delivery as in the case of whey, zeins and gliadins [ 11 , 12 , 13 ]. In this context, the use of techniques that allow the analysis of protein solutions to determine the presence of aggregates in a fast, reproducible and qualitative way is of key importance.…”
Section: Setting the Frame And Initial Considerationsmentioning
confidence: 99%
“…On the other hand, the aggregation capability of proteins from natural sources is used to generate nanoparticles for drug-delivery as in the case of whey, zeins and gliadins [ 11 , 12 , 13 ]. In this context, the use of techniques that allow the analysis of protein solutions to determine the presence of aggregates in a fast, reproducible and qualitative way is of key importance.…”
Section: Setting the Frame And Initial Considerationsmentioning
confidence: 99%
“…In any case, by looking at the samples with a 9:1 ratio, only evaluated during the first four days, it is again observed that the MD matrix seems to be less efficient at blocking secondary oxidation. As a consequence of the observations related to PV and ATR-FTIR experiments, the protein seems to block or reduce the extension of the secondary oxidation reactions by blocking more efficiently UV light [44,45] and serving as gas and organic vapor barrier material at ambient conditions, compared to the polysaccharide. After careful examination and characterization of the different changing features in the spectra of the purposely oxidized encapsulates, it was decided that the safer parameter to be used to assess the oxidative effect, particularly in regard to secondary oxidation, was the band broadening of the carbonyl band at ca.…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…In any case, by looking at the samples with a 9:1 ratio, only evaluated during the first four days, it is again observed that the MD matrix seems to be less efficient at blocking secondary oxidation. As a consequence of the observations related to PV and ATR-FTIR experiments, the protein seems to block or reduce the extension of the secondary oxidation reactions by blocking more efficiently UV light [44,45] and serving as gas and organic vapor barrier material at ambient conditions, compared to the polysaccharide. Figure 5b,c show, as an example, the spectra of the raw materials, whey protein concentrate and maltodextrin respectively, before and after 4 days of UV light exposure.…”
Section: Oxidative Stabilitymentioning
confidence: 99%
“…However, food proteins have other functional properties including the ability to produce a thick film around oil droplets [1,9]. Among various food proteins, milk proteins are the most commonly used natural emulsifiers in food industry due to their amphiphilic nature, GRAS status, high nutritional value, and good sensory properties [11,12]. In addition, binding abilities of milk proteins to lipophilic bioactive compounds and ions and antioxidant activity make them suitable for the encapsulate and protect bioactive compounds efficiently [11,12].…”
Section: Milk Proteins As Emulsifiersmentioning
confidence: 99%
“…Although various synthetic (e.g., monoglyceride, sucrose esters, polyglycerol esters) polymers have been used as emulsifiers in food industry, there has been an increase in demand for 'clean' label food, which can make food manufacturers use natural emulsifier for food application [2,3]. Among natural emulsifiers, milk proteins, such as casein and whey proteins, have several benefits for the formation of emulsion-based delivery system due to their amphiphilic characteristics, GRAS status, excellent nutritional value, and various functionalities [10][11][12].…”
Section: Introductionmentioning
confidence: 99%